TASK-BASED LANGUAGE TEACHING (TBLT) IN TEACHING ENGLISH AND GERMAN: COMPARATIVE STUDY (TAMADDUN NURI JURNALI, 2025)
Task-Based Language Teaching (TBLT) represents a contemporary, learner-centered methodology that prioritizes real-world task completion as a means of acquiring language skills. This paper examines the theoretical underpinnings of TBLT and compares its implementation in English and German language education, with a particular focus on the Uzbek educational context. While TBLT promotes communicative competence in both languages, English benefits from greater resource availability and global usage, whereas German instruction faces obstacles such as structural complexity and limited methodological support. The study explores how factors like teacher readiness, curriculum design, student motivation, and assessment practices influence the effectiveness of task-based instruction. It also emphasizes the need for localized adaptations and targeted teacher training to ensure successful integration. The findings suggest that when thoughtfully applied, TBLT can significantly enhance learner engagement and language proficiency across diverse linguistic contexts.